Plasticity and Fracture - Brocks, Wolfgang; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book is based on 40 years of research and teaching in the fields of fracture mechanics and plasticity. It will bring students and engineers from various disciplines up to date on key concepts that have become increasingly important in the design of safety-relevant engineering structures in general and in modern lightweight structures in the transportation industry in particular. Primarily intended for graduate students in the engineering sciences and practicing structural engineers, it employs a multidisciplinary approach that comprises theoretical concepts, numerical methods, and experimental techniques. In addition, it includes a wealth of analytical and numerical examples, used to illustrate the applications of the concepts discussed.
1 Introduction -- 2 Concepts of fracture mechanics -- 3 Phenomenological theory of time- and rate-independent plasticity -- 4 Extension of LEFM for small-scale yielding -- 5 Path-independent integrals --  6 Asymptotic solution of the stress and strain field at the crack tip in EPFM -- 7 Slip line theory -- 8 Plastic collapse and limit load -- 9 Determination of fracture parameters.
Keywords: Mechanics, Applied; Solids; Building materials; Mathematics -- Data processing; Machinery; Solid Mechanics; Structural Materials; Computational Science and Engineering; Machinery and Machine Elements